Farrerol Modulates Aorta Gene Expression Profile in Spontaneously Hypertensive Rats - Qin, Xiaojiang; Hou, Xiaomin; Zhang, Kun; Li, Qingshan (Planta Medica, 2018)
Farrerol, a typical natural flavanone and major active component in Rhododendron dauricum var. ciliatum, has been shown to possess vasoactive ability in vitro. The aim of this study was to investigate its effect on aorta gene expression in spontaneously hypertensive rats. Twelve-week-old male normotensive Wistar Kyoto rats and spontaneously hypertensive rats were treated with orally administered farrerol (50 mg/kg body weight) for 8 wk before they were sacrificed. We found that aorta samples showed 444 upregulated genes in control spontaneously hypertensive rats compared with the control Wistar Kyoto rats. Administration of farrerol in spontaneously hypertensive rats increased the expression of 2329 genes in the aorta compared with the control spontaneously hypertensive rats. Gene expression profiles performed on the aorta revealed that farrerol induced changes in vascular smooth muscle contraction, mitogen-activated protein kinase signaling pathway, regulation of actin cytoskeleton, vascular endothelial growth factor signaling pathway, calcium signaling pathway, and renin angiotensin system. Furthermore, 10 genes involved in the pathway of vascular smooth muscle contraction were verified using real-time polymerase chain reaction technique, and several novel potential target genes for the farrerol treatment of hypertension were identified. The findings of this study lend support to the potential use of farrerol as a novel therapeutic and antihypertensive candidate drug to prevent the development of hypertension.
Keywords: flavanone; Ericaceae; farrerol; Rhododendron dauricum; gene expression profile; aorta; spontaneously hypertensive rat